Environmental training in higher education: Construction of Knowledge and Practices from Geography (Huellas, 2026)
In the field of Higher Education, it is essential to highlight the experiences of teachers and students in order to promote transdisciplinary dialogue and reflect on the challenges posed by addressing environmental issues for the various actors within the university context. The selection, organization, and sequencing of environment-related content facilitate the acquisition of tools and meaningful learning experiences necessary to adopt a committed stance toward environmental care. Geography can provide conceptual frameworks and analytical approaches to understand the complexity of the relationships that are woven when society makes sustainable use of nature; at the same time, it offers methodological tools to address environmental issues and foster responsible attitudes and practices in relation to the environment. The aim is to disseminate the experiences of university teachers and students related to environmental topics within the context of the course Techniques in Geography at the Universidad Nacional del Sur for the 2015–2025 period. The results highlight the value of a transdisciplinary approach and fieldwork in university environmental education and raise new questions regarding the teaching and dissemination of environmental research at the higher education level.
Keywords: Higher Education; Qualitative and Quantitative Methods; Geography; Environmental Education; Transdisciplinarity